The Darkest Hue (Instagram, 2021)
"Jeymes Samuel isn’t much more imaginative than white Hollywood writers and directors. He can’t imagine Stagecoach Mary looking how she did- a beautiful fat, tall, dark-skinned Black woman- and being desired. His casting choices may reflect his *gendered* colorist biases. He hand-picked dark-skinned, monoracial Black actors to play the big, strong, and tough cowboys, despite most of the real-life male characters being fair-complected and mixed-raced. The first person he chose to be Stagecoach Mary was Erykah Badu, a light-brown skinned, thin, and green-eyed Black woman in his 2013 short film They Die by Dawn. He recently chose Zazie Beatz, a light-skinned biracial actress, to play Stagecoach Mary. This infographic essay explores what could have informed these decisions. Light skinned and biracial actresses also have a responsibility to turn down these roles (see slide 9). Don't forget to support me (last slide) if you're able to! #colorism #stagecoachmary #zaziebeetz #thehardertheyfall #jeymesamuel #explorepage #explorepage"
Keywords: 2000 à aujourd'hui; approches et analyses; colorisme; corps; cours; fem3300; intersectionnalité; militance; premier cycle; périodes historiques; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; violences

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences